2016
DOI: 10.18203/2394-6040.ijcmph20162542
|View full text |Cite
|
Sign up to set email alerts
|

Perception of pregnant women towards caesarean section in Nigeria: a case study of a missionary hospital in EDO, Nigeria

Abstract: INTRODUCTIONCaesarean section is a surgical procedure in which one or more incisions are made through a mother's abdomen (laparotomy) and uterus (hysterotomy) to deliver one or more babies, or to remove a dead fetus.1 It is one of the most important operations performed in obstetrics and gynaecology. Its life saving value to both mother and fetus has increased over the decades although specific indications for its use have changed. Its purpose of preserving the life of a mother with obstructed labour and deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The decision-making process for the woman involves a multiplicity of factors which include knowledge of the CS process, finances and family support [ 10 , 14 ]. Osamor and Grady [ 15 ] in an integrative literature review of studies in Africa, South and Central Asia observed that women's decision-making regarding their healthcare seems not to be fully autonomous.…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making process for the woman involves a multiplicity of factors which include knowledge of the CS process, finances and family support [ 10 , 14 ]. Osamor and Grady [ 15 ] in an integrative literature review of studies in Africa, South and Central Asia observed that women's decision-making regarding their healthcare seems not to be fully autonomous.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from studies in Nigeria and Ghana indicate that some traditional women are unwilling to have caesarean section because of the general belief that abdominal delivery is reproductive failure on their part, and others for fear of mockery [18][19][20]. Chigbu and Iloabachie [19] found a high prevalence of caesarean section refusal among their study participants and noted very poor maternal and perinatal outcomes as a result of this refusal.…”
Section: Introductionmentioning
confidence: 99%
“…Informed refusals especially when the fetus's life is at risk is challenging. Factors that might influence these decisions include fear of postoperative pain, increased facility costs, cultural and religious beliefs, family/partner objection, lack of knowledge of the consequences and fear of death for both mother and child [37,38]. One Nigerian study (n=413) reported of mothers (12%) unwilling to accept the procedure under any circumstance [36].…”
Section: Aversion Towards Csmentioning
confidence: 99%
“…One Nigerian study (n=413) reported of mothers (12%) unwilling to accept the procedure under any circumstance [36]. Reports of refusals are mostly from low income countries [34,35,38], but a small proportion are also reported from high income countries [37].…”
Section: Aversion Towards Csmentioning
confidence: 99%